Concomitant sensitization to legumin, Fag e 2 and Fag e 5 predicts buckwheat allergy - Geiselhart, S.; Nagl, C.; Dubiela, P.; Pedersen, A. C.; Bublin, M.; Radauer, C.; Bindslev‐Jensen, C.; Hoffmann‐Sommergruber, K.; Mortz, C. G. (Clinical and experimental allergy, 2018)
Summary Background Buckwheat (Fagopyrum esculentum) has become increasingly popular as a healthy food in Europe. However, for sensitized individuals, consumption can cause anaphylactic reactions. The aim of this study was to identify individual well‐characterized buckwheat allergens for component‐resolved diagnosis. Methods Patients were selected by positive skin prick test to buckwheat and divided into two groups: (1) sensitized to buckwheat without clinical symptoms and (2) buckwheat allergy. Buckwheat proteins were extracted from raw buckwheat seeds, purified applying a combination of protein precipitation and chromatographic methods, and analyzed by IgE immunoblotting and ELISA. Results Buckwheat‐allergic patients had a significantly larger median skin prick test weal diameter for buckwheat than the sensitized group and the positive control. Also, IgE immunoblotting clearly showed a distinct pattern in sera from allergic patients when compared to sensitized individuals. Several IgE‐reactive proteins were purified from crude buckwheat extract, namely legumin (Fag e 1 plus its large subunit), Fag e 2 (2S albumin), and newly identified Fag e 5 (vicilin‐like) as well as hevein‐like antimicrobial peptides, designated Fag e 4. All four allergens showed superior diagnostic precision compared to extract‐based ImmunoCAP with high sensitivity as well as high specificity. Conclusions Patients with clinical symptoms clearly show a distinct allergen recognition pattern. We characterized a buckwheat vicilin‐like protein as a new relevant marker allergen, designated Fag e 5. Additionally, another new allergen, Fag e 4, potentially important for cross‐reactivity to latex was added to the allergen panel of buckwheat. Further, our data show that the full‐length legumin comprising both, large and small subunit should be applied for component‐resolved diagnosis. Our data indicate that concomitant sensitization to legumin, Fag e 2 and Fag e 5, predicts buckwheat allergy.